Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

Reactivation of abandoned oilfields for cleaner energy generation: Two-dimensional modelling of lateral stratigraphic variations - Benjamin M. Storey; Richard H. Worden; David D. McNamara; John Wheeler; Julian Parker; Andre Kristen (Marine and Petroleum Geology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biomimetic Dissolution: A Tool to Predict Amorphous Solid Dispersion Performance - Michael M. Puppolo; Justin R. Hughey; Traciann Dillon; David Storey; Susan Jansen-Varnum (AAPS PharmSciTech, 2017)

Rheomorphic ignimbrites of the Rogerson Formation, central Snake River plain, USA: record of mid-Miocene rhyolitic explosive eruptions and associated crustal subsidence along the Yellowstone hotspot track - Thomas R. Knott; Marc K. Reichow; Michael J. Branney; David R. Finn; Robert S. Coe; Michael Storey; Bill Bonnichsen (Bulletin of Volcanology, 2016)

The regulation of AMPK signaling in a natural state of profound metabolic rate depression - Christopher J. Ramnanan; David C. McMullen; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Expression of Nrf2 and its downstream gene targets in hibernating 13-lined ground squirrels, Spermophilus tridecemlineatus - Pier Jr Morin; Zhouli Ni; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2008)

UDP-sugar pyrophosphorylase is essential for pollen development in Arabidopsis - Judy A. Schnurr; Kathleen K. Storey; Hans-Joachim G. Jung; David A. Somers; John W. Gronwald (Planta, 2006)

Development of a New Approach to Cumulative Effects Assessment: A Northern River Ecosystem Example - Monique Dubé; Brian Johnson; Gary Dunn; Joseph Culp; Kevin Cash; Kelly Munkittrick; Isaac Wong; Kathlene Hedley; William Booty; David Lam; Oskar Resler; Alex Storey (Environmental Monitoring and Assessment, 2006)

HIF-1α involvement in low temperature and anoxia survival by a freeze tolerant insect - Pier Morin; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Quantitative Determination of the Extent of Neutralization of Carboxylic Acid Functionality in Carbopol® 974P NF by Diffuse Reflectance Fourier Transform Infrared Spectrometry Using Kubelka-Munk Function - Rong-Hwei Juang; David E. Storey (Pharmaceutical Research, 1998)